The Social Approach in Understanding Tafsir Hukmi: Bridging Text and Context - Ahmad Ajik Nur Fata Mubarok; Eni Zulaiha; Isa Imadussalam Alfani (Tunas Harapan Ummat Foundation, 2025)
Tafsir hukmi is a method of Qur'anic interpretation that focuses on legal verses (ayat al-ahkam) related to Islamic law. The background of this study highlights the need for a deeper understanding of tafsir hukmi, particularly in its historical development, relevance, and application to Islamic jurisprudence. This method emerged alongside the growing necessity for Muslims to comprehend the legal aspects of the Qur'an, both textually and contextually, especially during the formation of the various schools of Islamic law. The objective of this article is to explore the definition of tafsir hukmi, review its historical evolution, and analyze the different scholarly views regarding literal and contextual approaches in this interpretation. The study employs a descriptive-analytical method through a literature review. Data were gathered from academic sources such as books, journals, and tafsir works related to tafsir hukmi. The analysis focuses on how tafsir hukmi was applied by scholars from the Prophet’s time through the development of legal schools, and the challenges it faces in addressing contemporary legal issues. The findings indicate that while tafsir hukmi provides clear legal guidance, it is also criticized for its limitations in addressing the broader spiritual and moral dimensions of the Qur'an’s message.